Protocol Development for Assessing Seed Moisture Content and Germination Testing in Amorphophallus muelleri Blume - Fadhilah, Siti; Widajati, Eny; Ilyas, Satriyas; Palupi, Endah Retno; Qadir, Abdul (Department of Agronomy and Horticulture, IPB University, 2025)
Seed quality testing involves the evaluation of germination capacity under a standardized moisture content. However, limited reports have been found for seed testing methodology, especially for Amorphophallus muelleri. Standardizing the seed testing method for A. muelleri is essential to ensure repeatability, reproducibility, and reliable seed germination results. This study aimed to develop procedures for assessing seed moisture content and germination tests. Three seed lots were used for seed moisture content determination. The necessity for seed cutting and efficacy of high-temperature oven methods (133°C for 4, 5, and 6 h) were compared to low-temperature oven methods (103°C for 17 h). Five lots of seeds of different ages were used for the seed germination test using the between-paper method in a constant temperature germinator of 25 and 30 °C. There was no significant difference in the moisture content between the uncut/whole and the seeds cut. The high temperature of 133°C for four hours is an alternative to the low temperature. Germination rates at 25 and 30°C had no significant difference, i.e., 84 to 97% and 83 to 99%, respectively. However, at 30°C, it was shorter to 50% germination (T50) and germination period. Preheating the seeds for four weeks using the dry heat method shortened the seed germination time from 57 to 37 days. Seed lot exposed to dry heat had half the time required to reach T50, or 16.4 to 31.9 days after treatment, with a germination period of 37 to 52 days. The first count of germination at 25°C without preheating was 47 days after planting, and the final count was 73 days after planting, whereas at 30OC, it was 37 and 57 days after planting. The first and final count for germination with preheating treatment at both temperatures was 20 DAP and 37 DAP.